PP11 Defining major trauma in the hyper acute setting. Issue 10 (25th September 2020) - Thompson, Lee; Hill, Michael; McMeekin, Peter; Shaw, Gary
Abstract : Background: Pre-hospital trauma is complex and challenging, with limited clinical exposure for clinicians. In addition, there is no standardised definition for major trauma, and retrospective scores commonly quantify injury severity, such as the injury severity score. This qualitative study aimed to explore the pre-hospital perspectives of major trauma and how pre-hospital trauma care providers define major trauma. Method: Three focus groups of 40–60 minutes duration were conducted with paramedics, ambulance technicians, police, firefighters and emergency dispatchers. Digital recordings were transcribed verbatim, coded and reviewed to identify emerging themes. Constant comparison was undertaken throughout and codes identified for qualitative thematic analysis. Results: Three overarching themes emerged: clinician factors, patient factors and situational factors. Clinician factors highlighted issues of experience and exposure (or lack of) to major trauma and its relationship to clinical concern, communication issues and the complex nature of pre-hospital trauma. Patient factors identified deranged physiology, actual injuries, life changing trauma, potential need for surgical intervention and rehabilitation as defining major trauma. These variables are often complicated by the extremities of age as well as previous medical history and medications. The situational factors identified that every traumatic encounter is unique, requiring bespoke management where high and low energy mechanisms of injury should be considered. Conclusion: Based on the analysis of the focus groups, a working pre-hospital definition is: Any injury (or injuries) that have the potential to be life-threatening or life-changing, including those sustained from low energy mechanisms in people rendered vulnerable by extremes of age, comorbidities or frailty, resulting in significant physiological compromise (haemodynamic instability, reduced consciousness, respiratory compromise) and/or significant anatomical abnormality that may require immediate intervention.